1972
DOI: 10.4141/cjas72-084
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Erucic Acid in Swine Tissue Lipids

Abstract: Swine were maintained for 6 weeks on practi-acids, whereas in the ovary, liver, kidney, and cal corn-soy diets containing l\Vo cornoil(Zea testis, only 1,-3Vo was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…As a result of the inclusion of fish oil in the experimental diets, the levels of EPA and DHA were increased in muscle and fat tissues according with previous observations (Leskanich et al, 1994). The increases in the levels of eicosenoic and erucic acids in the tissues, particularly within the adipose tissue, have been observed previously when rapeseed oil has been fed (Walker, 1972).…”
Section: Discussionsupporting
confidence: 66%
“…As a result of the inclusion of fish oil in the experimental diets, the levels of EPA and DHA were increased in muscle and fat tissues according with previous observations (Leskanich et al, 1994). The increases in the levels of eicosenoic and erucic acids in the tissues, particularly within the adipose tissue, have been observed previously when rapeseed oil has been fed (Walker, 1972).…”
Section: Discussionsupporting
confidence: 66%
“…The results of the plasma fatty acid analyses are summarized in Tables I and2.In general, the largest differences were found in the 18:1n-9 and 18:2n-6 levels of sow plasma, with smaller but more consistent changes in the saturated fatty acids. Walker (1972) also noted that, except for the mono and dienoic fatty acids, swine tissue (including plasma) fatty acid patterns failed to reflect dietary patterns. It is noteworthy that, although the sows eating the basal diet and soybean oil added diet were receiving the same amount of 18:2n-6 in the dietary fat, the area percent l8l.2n-6 levels in the plasma of the soybean oil added animals was much higher.…”
mentioning
confidence: 99%
“…Earlier studies indicated that pigs do not accumulate excessive amounts of cardiac lipids when fed diets containing rapeseed oil (RSO) nor was much erucic (A-13-cTs-docosenoic) acid (22:1) incorporated into heart (1 -7 ), or other tissues (2,3,6). Recently, lipid globules were detected by electron microscopy in myocardial cells of pigs fed RSO-containing diets (8).…”
Section: Introductionmentioning
confidence: 99%